Pengaruh Rasio Keuangan terhadap Harga Saham: Studi pada Perusahaan Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Duta Arya; Mayar Afriyenti (Universitas Negeri Padang, 2026)
This study will track the stock prices of consumer goods companies listed on the IDX and look at how financial ratios relate to those stock prices. Investors may see the relationship between the independent variables (share price) and the dependent variable (EPS, NPM, PER, and PBV) in this table. A causal associative design is the basis of the quantitative method employed. The IDX's publicly available stock price data and annual financial reports served as the secondary sources for this study's data. The purposive sampling process resulted in a sample size of twenty-four consumer products companies. Over the course of four years, a total of 96 observations were made. Our REM-based panel data regression analysis was conducted in EViews 13. It appears that stock prices and net profit margin (NPM) are positively and statistically significantly related, whereas earnings per share (EPS), price-to-book value (PBV), and PER are not. These findings suggest that when assessing a company's performance, investors in the consumer goods sector place a higher emphasis on net profitability than on market-based measures such as PER and PBV. Businesses and investors alike can benefit from the study's findings, which contribute to the expanding corpus of knowledge on financial management and provide practical advice for improving operational efficiency, sustaining stock price confidence, and making more informed investment decisions.